2023
DOI: 10.3390/ani13061090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fishmeal Replacement by Clostridium Autoethanogenum Protein Meal on Cholesterol Bile Acid Metabolism, Antioxidant Capacity, Hepatic and Intestinal Health of Pearl Gentian Grouper (Epinephelus Fuscoguttatus ♀ × Epinephelus Lanceolatus ♂)

Abstract: In this study, we present data from an eight-week growth trial with pearl gentian grouper fed either a reference diet (FM) with a fishmeal level of 50%, or test diet wherein 15% (CAP15), 30% (CAP30), 45% (CAP45), and 60% (CAP60) fishmeal was replaced by Clostridium autoethanogenum protein meal (CAP). Results showed that the weight gain and daily feed intake ratio of CAP60 were significantly lower than the FM group. In the serum, compared to the FM group, the content of malondialdehyde (MDA), the activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…In both turbot trials, the FI linearly decreased with the increasing of dietary CAP. The same phenomenon was also observed on M. salmoides (Yang et al 2022a), L. crocea (Wu et al 2022) and pearl gentian grouper (Huang et al 2023). These works indicated that low palatability of CAP should be concerned, especially in carnivorous sh feed.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In both turbot trials, the FI linearly decreased with the increasing of dietary CAP. The same phenomenon was also observed on M. salmoides (Yang et al 2022a), L. crocea (Wu et al 2022) and pearl gentian grouper (Huang et al 2023). These works indicated that low palatability of CAP should be concerned, especially in carnivorous sh feed.…”
Section: Discussionsupporting
confidence: 69%
“…The present work conformed the safety of CAP. However, the mucosal fold height in MI and density in DI were signi cantly reduced by CAP, which was similar with L. crocea (Lu et al 2021), M. salmoides (Yang et al 2022b) and pearl gentian grouper (Huang et al 2023). This disadvantage could be attributed to excessive isoleucine and valine brought by CAP.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, no toxic genes found in the complete genome sequence of C. autoethanogenum indicated that CAP has low risk potential (Norman et al 2018). Recently, CAP was proved to successfully replace certain amount of shmeal in the feed of black sea bream Acanthopagrus schlegelii (Chen et al 2020), largemouth bass Micropterus salmoides (Lu et (Huang et al 2023), puffer sh Takifugu obscurus (Cui et al 2022) or soybean meal in the feed of grass carp Ctenopharygodon Idella (Fan et al 2022;Xue et al 2023), Jian carp Cyprinus carpio var. Jian (Li et al 2021) and tilapia Oreochromis niloticus (Maulu et al 2021a, b).…”
Section: Introductionmentioning
confidence: 99%
“…For sensory quality, the muscle texture in largemouth bass ( Yang et al., 2022b ), large yellow croaker ( Wu et al., 2022 ) and grass carp ( Fan et al., 2022 ; Xue et al., 2023 ), flavor in largemouth bass ( Yang et al., 2022b ) and grass carp ( Xue et al., 2023 ), and skin color in large yellow croaker ( Wu et al., 2022 ) were affected by CAP inclusion. Although studies investigated the transcription of muscle-related genes altered by CAP ( Fan et al., 2022 ; Huang et al., 2023 ; Zheng et al., 2022 ), the molecular mechanisms of how CAP affects fish quality remain unclear.…”
Section: Introductionmentioning
confidence: 99%